Performance of TEC Cascade on Input Voltage Variations in Fish Cooler Box - Zuryati Djafar; Sabiqunnas sabiqun; Wahyu Haryadi Piarah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2022)
The refrigeration system used to meet the needs of human life can be in the form of a thermoelectric cooler (TEC). Due to its small volume, environmental friendliness and several other advantages, TEC can be widely applied such as in fish cooler box. In this study, the cooler box used had dimensions of 290mm x 205mm x 254mm and were given twelve stacked 3 TEC modules with varied DC voltages. The purpose of this study is to determine the voltage that can provide the best TEC performance. This performance will be indicated by the Coefficient of Performance (COP) value of each voltage variation. The experimental results show that the best performance of the TEC is at 42 Volts. The lowest temperature achieved during the experiment was 7.74℃ on the cold-side.